2006
DOI: 10.1021/jm050232e
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of New Tetrazolyl- and Carboxy-biphenylylmethyl-quinazolin-4-one Derivatives as Angiotensin II AT1 Receptor Antagonists

Abstract: A series of novel quinazolin-4-ones was designed and their molecular modeling simulation fitting to a new HipHop 3D pharmacophore model using CATALYST was examined. Several compounds showed significant high simulation fit values. The designed compounds were synthesized and eight of them were biologically evaluated in vitro using an AT1 receptor binding assay, where compound XX competed weakly against radiolabeled Sar1Ile8-angiotensin II (Ang II) binding, compounds XIV and XXII showed moderate competition, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
64
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(66 citation statements)
references
References 45 publications
2
64
0
Order By: Relevance
“…The low percentage of the retrieved molecules of the databases proved the high selectivity of such hypothesis. 21 In addition, it was found that the ACEI molecules; 3, 4, and 5 ( Fig. 1), that exist among the used databases molecules, were among the recognized mapped molecules in this search.…”
Section: Introductionmentioning
confidence: 72%
“…The low percentage of the retrieved molecules of the databases proved the high selectivity of such hypothesis. 21 In addition, it was found that the ACEI molecules; 3, 4, and 5 ( Fig. 1), that exist among the used databases molecules, were among the recognized mapped molecules in this search.…”
Section: Introductionmentioning
confidence: 72%
“…Quinazoline-2,4-diones are one of the important heterocycles 1 and have been shown to possess pharmacologically interesting properties such as anti-hypertensive, 2 antidiabetic, 3 and immunosuppressive activities. 4 Among these, synthetic pelanserine (TR2515) (1) 5 is a well established potent anti-hypertensive, having activity comparable to ketanserin, 6 which is an anti-hypertensive agent used clinically.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery by DuPont of the first potent and orally active non-peptide AII antagonist losartan [10] has stimulated extensive research interest in this area. Several patents and publications have appeared over the past few years [11,12] describing new AII receptor antagonists including candesartan, irbesartan, valsartan, telmisartan, tasosartan and eprosartan, which have been proven safe and effective in the treatment of hypertension and other cardiovascular disorders [13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%